2015
DOI: 10.1038/tp.2015.174
|View full text |Cite
|
Sign up to set email alerts
|

Subthreshold depression is associated with impaired resting-state functional connectivity of the cognitive control network

Abstract: Subthreshold depression (StD) is a prevalent condition associated with social morbidity and increased service utilization, as well as a high risk of developing into a major depressive disorder (MDD). The lack of well-defined diagnostic criteria for StD has limited research on this disorder, with very few brain-imaging studies examining the neurobiology of StD. Yet, identifying the neural pathology of StD has the potential to elucidate risk factors and prognostic markers for major depression and is crucial for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 67 publications
6
68
0
1
Order By: Relevance
“…This result is consistent with previous resting state FC studies in StD patients (Hwang, Egorova, 2015, Li et al, 2014b, Ma et al, 2013). In a previous study, Ma and colleagues (Ma, Li, 2013) compared regional homogeneity (ReHo) changes of late-life individuals with StD to controls.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This result is consistent with previous resting state FC studies in StD patients (Hwang, Egorova, 2015, Li et al, 2014b, Ma et al, 2013). In a previous study, Ma and colleagues (Ma, Li, 2013) compared regional homogeneity (ReHo) changes of late-life individuals with StD to controls.…”
Section: Discussionsupporting
confidence: 93%
“…In another study on the same cohort of StD patients, Li and colleagues (Li, Ma, 2014b) found the StD group showed increased regional amplitude of low-frequency fluctuation (ALFF) in the anterior portion of the dorsal ACC (adACC), which also displayed increased FC with the dorsolateral prefrontal cortex and supplementary motor area, and decreased FC with the anterior insula, thalamus, and putamen. In a more recent study (Hwang, Egorova, 2015), based on the same data set, we found a significant resting state FC decrease between the DLPFC and the temporo-parietal junction (TPJ)/precuneus (the brain regions associated with the representation of self and other mental states) and the insula in StD subjects.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…rsFC allows for the study of the function of one or several brain regions in relation to its functional network and how the network contributes to brain procedures (Hwang et al, 2015; Jessica S. Damoiseaux & Greicius, 2009). It has also widely been used to reveal the underlying mechanisms of different diseases (Sun et al, 2012; J.…”
Section: Introductionmentioning
confidence: 99%
“…However, a related study performed on regular meditators and non-meditators suggests that repeated meditation training may be able to raise the efficiency of neural networks mobilized for task based attention and impulse control [24]. These neural activities recruited may activate default-mode network [25,26] that is an important role of depression [26], and promote precuneus structural changes [6] to elicit happy emotions and helped the patient or subject to produce psychological activities. In conclusion, the findings of our study suggests that during short term loosen up meditation increased percentage content and median power frequency of α-wave, and also increased sympathetic nerve activity in young subjects.…”
Section: Discussionmentioning
confidence: 99%